TEKNIK BIBLIOKONSELING UNTUK MENINGKATKAN KEPERCAYAAN DIRI SISWA - Aminah, Asti Siti (2015)
This research purpose to examined of Bibliocounseling technique to increase student confidence grade VIII SMP N 1 Majalaya. This research used quantitative approach. Research methode used quasi eksperimental methode with single subject research A-B design. Research subject is student not confidence in grade VIII SMPN 1 Majalaya (N = 4 Students). Self confidence in this context was measured by instrument based Lautser Self Confidence aspect included 1) have self efficacy, 2) optimist, 3) responsibility, 4) rasional and realistic, 5) tolerance. This study used descriptive statistical for analyed gain self confidence score and analyzed baseline A and B. Result showed that Bibliocounseling technique was effective for increase self confidence. This research advice for guidence and counseling teacher, department phsychology education and guidence, and next research.